1995
DOI: 10.1002/jsfa.2740680319
|View full text |Cite
|
Sign up to set email alerts
|

The solubilisation and hydrolysis of spinach cell wall polysaccharides in gastric and pancreatic fluids

Abstract: Abstract:The aim of this work was to investigate the fate, in the upper gut of a monogastric animal, of polymers bound within plant cell walls. Uniformly and specifically 14C-labelled spinach cell walls were incubated in artificial body fluids with and without pepsin or pancreatin. In the absence of enzymes, artificial pancreatic juice (pH 8.8) at 37°C hydrolysed the methyl ester groups of wall-bound pectins [half-life (t1,2) 25 h]; the O-acetyl ester groups of cell wall polysaccharides were much more stable (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Under simulated conditions of the stomach and small intestine some solubilization of labelled uronate residues from spinach CW was observed, although the solubilized material was polymeric and there was no evidence of degradation to oligogalacturonides or monosaccharides (Miller et al 1995). In agreement with this observation, only small amounts of 14C were solubilized during passage through the small intestine of the rat, but on reaching the caecum the 14C became rapidly soluble.…”
Section: Digestion O F Uronate-6-'4c-labelled C E L L Walls In T H E supporting
confidence: 70%
See 2 more Smart Citations
“…Under simulated conditions of the stomach and small intestine some solubilization of labelled uronate residues from spinach CW was observed, although the solubilized material was polymeric and there was no evidence of degradation to oligogalacturonides or monosaccharides (Miller et al 1995). In agreement with this observation, only small amounts of 14C were solubilized during passage through the small intestine of the rat, but on reaching the caecum the 14C became rapidly soluble.…”
Section: Digestion O F Uronate-6-'4c-labelled C E L L Walls In T H E supporting
confidence: 70%
“…Artificial pancreatic juice caused the slow, non-enzymic removal of methyl ester groups (half-life 25 h) from intact CW containing [~nethyl-~~CJpectin (Miller et al 1995). However, since the CW are only present in the upper gut for 2-3 h, non-enzymic hydrolysis can only account for the release of a small proportion of the methyl ester residues in the upper gut.…”
Section: Digestion Of Cell-wall Methyl and Acetyl Ester Groups I N T mentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrolysis resulted in release of reducing sugars and fragments of the pectin linear chain. Miller et al (1995) also reported limited hydrolysis of ester bonds in spinach cell wall pectins, being the methyl ester groups more resistant of the O-acetyl groups at pH 1.8 whereas the opposite was observed at pH 8.8. In comparison to pectins and arabinoxylans, b-glucan is resistant to very low pH for long times (Johansson et al, 2006).…”
Section: Structural and Chemical Changes Of Df During Digestionmentioning
confidence: 91%
“…Beside structural changes, DF undergoes chemical changes in the upper intestine. By definition DF is resistant to hydrolysis by human digestive enzymes yet pancreatic lipase and other esterases might exert some hydrolytic activity toward methyl esters, O-acetyl esters, and N-acetylamide groups in DF molecules (Miller et al, 1995). At the very low pH of the stomach, the glycosidic linkages between component monosaccharides and ester linkages can suffer acid hydrolysis.…”
Section: Structural and Chemical Changes Of Df During Digestionmentioning
confidence: 99%